Non-canonical autophagy LAPs lupus. - Simon, A; Clarke, A (Nature Publishing Group, 2016)
Systemic lupus erythematosus (SLE) is an autoimmune disease whose central pathology is the recognition of, and reaction against, nuclear self-antigens by the immune system. This leads to type I interferon signalling, and the production of pathogenic auto-antibodies, which mediates much of the disease. The clinical consequences of the autoimmune response can be severe – common manifestations include rash, renal inflammation progressing to kidney failure, and neuropsychiatric involvement. The prevalence of SLE is approximately 0.1% – but why is it not much higher, given that many billions of cells die each day as part of normal tissue homeostasis? In the 5th May issue of Nature, Martinez et al.1 provide a new insight into how these apoptotic cell corpses are removed before they can incite an inflammatory response. Phagocytosis of apoptotic cells is performed by macrophages and immature dendritic cells, and it is known that genetic variants affecting components of this process (e.g., ITGAM2) can predispose to SLE. Similarly, deletion of many of the genes required for phagocytosis of apoptotic cells leads to a lupus-like disease in mice.3 Genome-wide association studies have consistently highlighted autophagy genes as risk loci in lupus,4 and Martinez et al. now show that one potential mechanism for this link is that a non-canonical form of autophagy, known as LC3-associated phagocytosis (LAP), is required for effective clearance of apoptotic cells (Figure 1).